2016
DOI: 10.1001/jamaneurol.2016.2549
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Glial Fibrillary Acidic Protein Astrocytopathy

Abstract: IMPORTANCE A novel astrocytic autoantibody has been identified as a biomarker of a relapsing autoimmune meningoencephalomyelitis that is immunotherapy responsive. Seropositivity distinguishes autoimmune glial fibrillary acidic protein (GFAP) meningoencephalomyelitis from disorders commonly considered in the differential diagnosis.OBJECTIVE To describe a novel IgG autoantibody found in serum or cerebrospinal fluid that is specific for a cytosolic intermediate filament protein of astrocytes.DESIGN, SETTING, AND … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
477
5
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 423 publications
(527 citation statements)
references
References 34 publications
17
477
5
5
Order By: Relevance
“…Despite the limited response to immunomodulatory treatments, the age, the gender, the clinical presentation, the CSF results, and the MRI changes in this patient were consistent with the novel autoimmune disorder autoimmune GFAP astrocytopathy [1-5]. …”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Despite the limited response to immunomodulatory treatments, the age, the gender, the clinical presentation, the CSF results, and the MRI changes in this patient were consistent with the novel autoimmune disorder autoimmune GFAP astrocytopathy [1-5]. …”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, our results showed that there was no pathological alteration of astrocytes (no loss of GFAP in the patient brain). This autoimmune astrocytopathy is probably mediated by antigen-specific cytotoxic T cells [1, 4]. Cytotoxic T cells specific for GFAP-derived peptides were shown to be pathogenic in a mouse model of autoimmune GFAP meningoencephalomyelitis where GFAP-specific CD8 + cytotoxic T cells caused various forms of central nervous system inflammation [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in animals or humans with this disease [1][2][3][4] . A human study at the Mayo Clinic showed that 13 patients responded well to initial intravenous high-dose steroid treatment, but 7 patients experienced relapse during dose tapering.…”
mentioning
confidence: 99%